2021
DOI: 10.1097/fjc.0000000000001051
|View full text |Cite
|
Sign up to set email alerts
|

MiR-4787-5p Regulates Vascular Smooth Muscle Cell Apoptosis by Targeting PKD1 and Inhibiting the PI3K/Akt/FKHR Pathway

Abstract: Vascular smooth muscle cell (VSMC) dysfunction is the main cause of aortic dissection (AD). In this study, we focused on the role and mechanism of miR-4787-5p in regulating VSMC apoptosis. Real-time fluorescence quantitative polymerase chain reaction was used to detect the expression of miR-4787-5p in aorta tissues of AD (n = 10) and normal aortic tissues of donors (n = 10). Cell apoptosis was tested by TUNEL assay and Annexin V FITC/PI staining flow cytometry. The expression of PC1 and the PI3K/Akt/ FKHR sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…[22][23][24] PI3K-Akt signaling plays an important role in phenotypic switching and apoptosis of human aortic vascular smooth muscle cells. [25][26][27] Those studies together with our results suggest that activated B cell-related DEGs may regulate the migration, apoptosis, and phenotype switch of smooth muscle cells to further affect the development of AD.…”
Section: Discussionmentioning
confidence: 58%
“…[22][23][24] PI3K-Akt signaling plays an important role in phenotypic switching and apoptosis of human aortic vascular smooth muscle cells. [25][26][27] Those studies together with our results suggest that activated B cell-related DEGs may regulate the migration, apoptosis, and phenotype switch of smooth muscle cells to further affect the development of AD.…”
Section: Discussionmentioning
confidence: 58%
“…Notably, expression levels of genes involved in PI3K/Akt signalling, contraction, and matrix degradation (GNG2, IGF1, ITGA2, LAMA1, LAMA4, COL6A3, ACTC1, MYL7, MMP24, and MMP16) were specifically enriched in stretched PM-SMCs, which may be relevant to their sensitivity to tension and ECM degradation. 38,39 Furthermore, we used LY294002, an inhibitor of PI3K/Akt signalling, for investigating the mechanism of tensile sensitivity in PM-SMCs and demonstrated that inhibition of PI3K/Akt signalling was able to reduce the sensitivity of PM-SMCs to stretching under low-strain stretching conditions.…”
Section: Discussionmentioning
confidence: 99%
“… 90 , 91 AKT can be also phosphorylated and activated by PDK2 at Ser473. 92 , 93 Activated AKT regulates cell proliferation, differentiation, migration, and apoptosis by activating or inhibiting downstream target proteins, such as Bad, 94 Caspase9, 95 NF-κB, 96 , 97 GSK-3, 98 FKHR, 99 , 100 p21, 101 p53 102 and FOXO1. 103 , 104 Aberrant activation of PI3K/AKT pathway has been found in a variety of cancers, 105 such as lung cancer, 106 esophageal cancer, 107 gastric cancer, 108 breast cancer, 109 laryngeal cancer, 110 gallbladder cancer, 111 and prostate cancer.…”
Section: The Pi3k/akt Signaling Pathway In Tumorigenesismentioning
confidence: 99%